2011
DOI: 10.1103/physreva.84.032106
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of decay of two identical quantum particles

Abstract: An analytical solution for the time evolution of decay of two identical non interacting quantum particles seated initially within a potential of finite range is derived using the formalism of resonant states. It is shown that the wave function, and hence also the survival and nonescape probabilities, for factorized symmetric and entangled symmetric/antisymmetric initial states evolve in a distinctive form along the exponentially decaying and nonexponential regimes. Our findings show the influence of the Pauli … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…We thus obtain the estimate 31) showing that the amplitude behaves for large times as an oscillatory function modulated by a decaying power law. Averaging over the oscillations, we obtain the following power-law decay for the mean echo:…”
Section: Asymptotic Analysis In the Long-time Regimementioning
confidence: 82%
“…We thus obtain the estimate 31) showing that the amplitude behaves for large times as an oscillatory function modulated by a decaying power law. Averaging over the oscillations, we obtain the following power-law decay for the mean echo:…”
Section: Asymptotic Analysis In the Long-time Regimementioning
confidence: 82%
“…An advantage of this method is that the decay width can be accurately calculated even when the width is extremely small [31,[53][54][55]. In the time-dependent framework, on the other hand, the quantum decay of a metastable state is treated as a time-evolution of a wave packet [56][57][58][59][60][61][62]. An advantage of this method is that the decay dynamics can be intuitively understood by monitoring the time-evolution of the wave packet.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent works [22][23][24][25][26][27][28] showed that particle statistics and contact interactions can deeply modify the decay dynamics. Fermions and bosons may show very different decay behaviour, in particular in many cases fermions tend to decay faster [22][23][24]. However, no experimental observation of this phenomenon has been reported yet.…”
mentioning
confidence: 99%
“…Experimental studies on Fano resonances [4], quantum decay processes [15,16] and bound states in the continuum [17][18][19][20][21] have focused up to now on single-particle dynamics. Interestingly, recent works [22][23][24][25][26][27][28] showed that particle statistics and contact interactions can deeply modify the decay dynamics. Fermions and bosons may show very different decay behaviour, in particular in many cases fermions tend to decay faster [22][23][24].…”
mentioning
confidence: 99%